A Potential Complication After Drainage in Odontogenic Descending Necrotizing Mediastinitis: Chyle Leakage. Issue 7 (20th October 2022) - Lou, Yiting; Weng, Xiaoyan; Zhuo, Qunhao; Ying, Binbin; Feng, Jiaxin; Wang, Huiming
Abstract : Abstract: Descending necrotizing mediastinitis is a serious complication of odontogenic infections. Incision and drainage of the maxillofacial infection with mediastinal drainage represent the principal management. However, chyle leakage after drainage in descending necrotizing mediastinitis is rare and has not been reported. Here the authors present a case of a 74-year-old man with chyle leakage after mediastinal drainage, which is successfully treated.